Local Resource Based Project For Learning Outcomes And Creativity In Coastal Schools: A Classroom Action Research - Muhammad Riswan Ramli; Yusmar Yusuf (JURNAL BIOEDUKASI, 2026)
This classroom action research aims to improve students' learning outcomes and creativity on the topics of Work, Force, and Simple Machines through the implementation of Project-Based Learning (PjBL) based on local resources. The research subjects were 20 eighth-grade students of SMP Negeri 30 Raja Ampat. The study was conducted in two cycles using the Kemmis & McTaggart model, which consists of the stages of planning, action, observation, and reflection. Data were collected through learning outcome tests, creativity observation sheets, interviews, documentation, and field notes. The results of the study showed an increase in the average learning outcome score from 67.80 to 89.35 (an increase of 31.78%), and an increase in student creativity from 69.50 to 87.65 (an increase of 26.12%). These findings indicate that project-based learning that utilises local potential can make science learning more contextual, meaningful, and collaborative in coastal schools.